2019
DOI: 10.3390/app9235132
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Activated Carbons Spent by Waste Water Treatment Using KOH Chemical Activation

Abstract: In this study, spent activated carbons (ACs) were collected from a waste water treatment plant (WWTP) in Incheon, South Korea, and regenerated by heat treatment and KOH chemical activation. The specific surface area of spent AC was 680 m2/g, and increased up to 710 m2/g through heat treatment. When the spent AC was activated by the chemical agent potassium hydroxide (KOH), the surface area increased to 1380 m2/g. The chemically activated ACs were also washed with acetic acid (CH3COOH) to compare the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…This was justified by the higher SSA and pore volume obtained with the CCA, suggesting that the steaming process cleared the pores of ash and allowed better N 2 adsorption than its nonactivated counterpart. This agrees with the work of Park et al [48] who reported that activation flushes out ash from the pore spaces leading to increased nitrogen adsorption.…”
Section: Bet Surface Area Isothermssupporting
confidence: 93%
“…This was justified by the higher SSA and pore volume obtained with the CCA, suggesting that the steaming process cleared the pores of ash and allowed better N 2 adsorption than its nonactivated counterpart. This agrees with the work of Park et al [48] who reported that activation flushes out ash from the pore spaces leading to increased nitrogen adsorption.…”
Section: Bet Surface Area Isothermssupporting
confidence: 93%
“…Furthermore, porosity in the range of mesopores facilitates the regeneration process of spent materials and the further multiple usage. The methods of regeneration most applied comprise wet oxidation, elution with suitable solvent, microwave or thermal regeneration [ 48 ]. The regeneration of adsorbents is important taking into account the assumptions of environmental sustainability and economic effectiveness [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, to enhance the adsorption capability of hydrochar, modification turned out to be an effective method [14]. By "modification" we mean a treatment in which the feedstock (hydrochar in this case) is treated with a chemical agent (e.g., KOH) via impregnation, which is not followed by a heat treatment at 500-850 • C in nitrogen typical of chemical activation [11,[15][16][17]. For instance, Regmi et al [18] tested the sorption capacities of KOH-modified hydrochar from switchgrass for removing copper and cadmium from aqueous solutions: they found a removal of about 100% within 24 h of contact time while the raw hydrochar only removed 16% of copper and 5.6% of cadmium.…”
Section: Introductionmentioning
confidence: 99%